A Tool for Teaching and Learning of Design Space Exploration on Processor Architectures - Amorim, Erick Rocha; Sovernigo, Felipe; Santos, Ricardo R. dos; Duenha, Liana (Anais da Escola Regional de Alto Desempenho do Centro-Oeste (ERAD-CO), 2023)
This paper presents a case study on the use of MultiExplorer as a tool for teaching and learning dark-silicon-aware design space exploration (DS-DSE) on multicore architectures in the context of undergraduate Computer Science and Computer Engineering programs in Brazil.